Analysis Quality of Services on and Satisfaction Loyalty Patients Sumberglagah Hospital Mojokerto - Bambang Priyono; Indasah Indasah; Koesnadi Koesnadi (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Hospitals were health facilities that provide individual health services including promotive, preventive, curative and rehabilitative services. Hospital services provided in the form of quality will be able to satisfy patients. Patients satisfied with the services provided can also create patient loyalty. This study aims to determine the effect of service quality on satisfaction and loyalty of patients at Sumber Glagah General Hospital Mojokerto. Research design used in this study a correlation analytic with a cross sectional approach. The population study were all in patients at Sumber Glagah General Hospital Mojokerto in August 2018 as many as 315 patients. The sampling technique used simple random sampling with a sample size of 100 patients. The independent variable was service quality and the dependent variable is satisfaction and loyalty. The instrument used a questionnaire that is tested for its validity and reliability. Data analysis used linear regression with a significance level of 0.05. The results showed that respondents stated that the services of the Sumberglagah General Hospital were of high quality at 56%. Respondents who stated that they were very satisfied were 94%. Respondents who stated were very loyal at 93%. The results of the linear regression test showed that p = 0.025 (α = 0.05) that H0 is rejected means that there is an influence between the quality of service of Sumberglagah Hospital in Mojokerto and patient satisfaction. The results of the linear regression test showed that p = 0.015 means that there is an influence between the quality of services of Sumberglagah Hospital in Mojokerto on patient loyalty. The quality of health services felt by patients is predicted to increase patient satisfaction. Good service quality will affect patient satisfaction as a hospital customer. The more quality the services provided by the hospital, the more patients will feel satisfaction with the services provided. The better quality of hospital services provided to patients will be more loyal patients to the hospital